Protecting the Ocular Surface in Cataract Surgery: The Efficacy of the Perioperative Use of a Hydroxypropyl Guar and Hyaluronic Acid Ophthalmic Solution - Favuzza E (Dove Medical Press, 2020)
Eleonora Favuzza, Michela Cennamo, Lidia Vicchio, Fabrizio Giansanti, Rita Mencucci Department of Neuroscience, Psychology, Pharmacology and Child Health (NEUROFARBA), Eye Clinic, University of Florence, Florence, ItalyCorrespondence: Rita MencucciDepartment of Neuroscience, Psychology, Pharmacology and Child Health (NEUROFARBA), Eye Clinic, University of Florence, Largo Brambilla 3, Florence 50134, ItalyTel +390557946975Email rita.mencucci@unifi.itPurpose: To evaluate the effects of a hydroxypropyl guar (HPG) and hyaluronic acid (HA) ophthalmic solution in terms of post-cataract surgery dry-eye disease (DED) prevention.Patients and Methods: In this retrospective study, the data of 419 patients not previously affected by DED, who had undergone unilateral cataract surgery in 17 Italian centers with different perioperative lubricating regimens, were retrospectively reviewed. Patients who had instilled HPG/HA solution 3 times/day in the preoperative week and for two postoperative months were included in group A; group B only instilled HPG/HA for two postoperative months; group C did not instill any perioperative artificial tears. All patients followed the same antibiotic and anti-inflammatory postoperative topical regimen. The scores of SPEED (Standard Patient Evaluation of Eye Dryness) questionnaire, tear break-up time (BUT) and corneal fluorescein staining (CFS, Oxford scale), performed at the preoperative visit and at one, four and eight postoperative weeks, were evaluated.Results: In groups A and B, the SPEED scores were significantly lower than group C in the whole postoperative period. In group A, the SPEED scores were significantly lower than group B 1 and 4 weeks after surgery (p< 0.001 and p=0.021). In group C, 25% of patients reported symptom scores corresponding to mild-moderate dry eye 4 and 8 weeks after surgery. The fluorescein tear BUT in groups A and B was significantly higher than group C in the whole postoperative period (p< 0.001). In group A, BUT was significantly higher than group B 4 weeks after surgery (p=0.016). More patients showed no corneal fluorescein staining (CFS grade=0) in groups A and B than group C at all the postoperative visits.Conclusion: The hydroxypropyl guar and hyaluronic acid ophthalmic solution was effective at reducing post-cataract surgery ocular discomfort and tear instability, particularly if also administered in the preoperative period.Keywords: dry eye, cataract surgery, artificial tears, hydroxypropyl guar, hyaluronic acid, ocular surface